Ambivalent Nature of Political Markets: Does It Undermine a Democracy? - М. А. Beznosov (Соціологічні студії, 2018)
This article is an attempt to analyze the contradictions of political marketing as a theory and technology. Various aspects of scholarly debate analyzed and various problems associated with application of political marketing are highlighted.